Information Technology Readiness and Acceptance Model for Social Media Adoption in Blended Learning Among Higher Educational Institutions in West Java, Indonesia - Yusuf, Fahmi (2024)
Technological developments, including the internet, and learning opportunities are increasing. This also causes learning strategies and models to develop. The blended learning model is applied in almost all universities in Indonesia and throughout the world. With so many universities in Indonesia, implementing blended learning is a challenge because it requires a lot of technological preparation and human resources; this often needs to be solved by policymakers in higher education. Blended learning requires a lot of strategies and technology to be implemented well. One of them is social media because social media has become a lifestyle for urban and remote communities to communicate. Based on the above, this research investigates the readiness and acceptance of social media information technology in blended learning to determine the factors that influence it among students in higher education. This research uses quantitative methods to develop a model by adopting concepts, theories and models such as information processing theory, technology readiness, technology acceptance, perceived validity and perceived trust, and information literacy theory. The number of respondents used was 384, and the purposive sampling technique was used in the student population in West Java. The novelty of the model developed is the addition of three new variables, namely information literacy, perceived validity, and perceived trust in the social media technology acceptance model in the application of blended learning. In the data processing results based on statistical tests, results were obtained that explained the 31 hypotheses constructed, 19 hypotheses were accepted, and 12 hypotheses were rejected. Information Literacy, Optimism, Innovativeness, Perceived Validity, Perceived Trust, Perceived Usefulness, Perceived Ease of Use, Intention to Use, and Usage Behavior are the accepted factors. The findings in this study contribute to academic knowledge and provide actionable insights for policymakers, institutions, and educational practitioners seeking to increase the acceptance and adoption of social media technologies in blended learning. The identified factors provide a strong foundation for strategic planning, policy development, and learning initiatives to encourage the successful adoption of social media technology in blended learning among private university students in West Java, Indonesia.